A concise history of Greece - Clogg, Richard, 1939- (New York : Cambridge University Press, 2013)
"Now re-issued in a third, updated edition, this book provides a concise, illustrated introduction to the modern history of Greece, from the first stirrings of the national movement in the late eighteenth century to the present day. The current economic crisis has marked a turning point in the country's history. This third edition includes a new final chapter, which analyses contemporary political, economic and social developments. It includes additional illustrations together with updated tables and suggestions for further reading. Designed to provide a basic introduction, the first edition of this hugely successful Concise History won the Runciman Award for the best book on an Hellenic topic published in 1992 and has been translated into twelve languages"--
"All countries are burdened by their history, but the past weighs particularly heavily on Greece. It is still, regrettably, a commonplace to talk of 'modern Greece' and of 'modern Greek' as though 'Greece' and 'Greek' must necessarily refer to the ancient world. The burden of antiquity has been both a boon and a bane. The degree to which the language and culture of the ancient Greek world was revered throughout Europe (and, indeed, in the United States where some of the founding fathers were nurtured on the classics) during the critical decades of the national revival in the early nineteenth century was a vital factor in stimulating in the Greeks themselves, or at least in the nationalist intelligentsia, a consciousness that they were the heirs to a heritage that was universally admired"--
Machine generated contents note: List of illustrations; Preface; 1. Introduction; 2. Ottoman rule and the emergence of the Greek state, 1770-1831; 3. Nation building, the 'great idea' and national schism, 1831-1922; 4. Catastrophe and occupation and their consequences, 1923-49; 5. The legacy of the civil war, 1950-74; 6. The consolidation of democracy and the populist decade, 1974-90; 7. Balkan turmoil and political modernization: Greece in the 1990s; 8. Greece in the new millennium: from affluence to austerity; Biographies; The royal houses of Greece; Presidents; Tables; Key dates; Guide to further reading; Index.
Includes bibliographical references and index.
Keywords: HISTORY / Europe / General; Greece -- History -- 1821-